Mapping the Unmapped Transit Network of Bogotá, Colombia (2018)
New tools have enabled “civic mappers” and transportation researchers to map previously unmapped transit networks that have been historically the purview of locals and insiders. These new datasets and maps show the extent of these systems while also enumerating basic operating characteristics, such as travel speed, route distance, frequency, and fare data. In this paper, the authors detail their process of visualizing Bogotá’s entire transit network, both the centrally-planned system of buses and the decentralized network of jitneys. By seeing the entire network, they argue that they can disentangle the development patterns of the city and monitor who has access to reliable transit, which also happens to be one of the United Nations’ Sustainable Development Goals. Since this type of work is still in its infancy, it is critical that researchers go out into the field and add more examples of how to do this work and share their process so different methodologies can be tested in different types of cities. In Bogotá, the authors, researchers from NYU’s Marron Institute of Urban Management worked with researchers and students from the Universidad del Rosario and the civic mapping community in Bogotá, used smartphones, cloud-based data managements systems, and mapmaking software to bring Bogotá’s unmapped transit network out of the shadows and put it on an equal footing with the established network of buses.